Tetraspanins in Mast Cells - Köberle, Martin; Kaesler, Susanne; Kempf, Wolfgang; Wölbing, Florian; Biedermann, Tilo (Frontiers in Immunology, 2012)
Mast cells are key mediators of the immune system, most prominently known for their role in eliciting harmful allergic reactions. Mast cell mediator release (e. g. by degranulation) is triggered by FcepsilonRI recognition of antigen – IgE complexes. Until today no therapeutic targeting of this and other mast cell activation pathways is established. Among possible new candidates there are tetraspanins that have been described on mast cells already several years ago. Tetraspanins are transmembrane proteins acting as scaffolds, mediating local clustering of their interaction partners and thus amplify their activities. More recently, tetraspanins were also found to exert intrinsic receptor functions. Tetraspanins have been found to be crucial components of fundamental biological processes like cell motility and adhesion. In immune cells, they not only boost the effectiveness of antigen presentation by clustering MHC molecules, they are also key players in all kinds of degranulation events and immune receptor clustering. This review focuses on the contribution of tetraspanins clustered with FcepsilonRI or residing in granule membranes to classical mast cells functions but also undertakes an outlook on the possible contribution of tetraspanins to newly described mast cell functions and discusses possible drugging strategies.